Peran Raden Ayu Lasminingrat dalam Mengembangkan Sekolah Keutamaan Istri Tahun 1907-1948 - Desi Harpiah; Eva Syarifah Wardah; Siti Fauziyah (Tsaqofah, 2018)
In the field of education, ethical politics has opened the way for indigenous people to make changes. However, the implementation of ethical politics has not fully given women the freedom to get formal education, especially in the Priangan area especially in the Limbangan area, Garut, West Java. The situation of women after the implementation of the Ethical Politics, especially in the Priangan area, most of the women were still bound by ignorance. Therefore, there were women who were concerned about education for women during the Dutch Colonial period. one of the characters namely Raden Ayu Lasminingrat born in 1843 in Limbangan Garut Regency is Princess Hoofd Penghulu Limbangan Garut namely Raden Haji Muhammad Musa.